Proceedings of the 14th International Conference on Local Mechanical Properties - LMP 2019 - Editorial, Foreword (Acta Polytechnica CTU Proceedings)
The 14th International Conference on Local Mechanical Properties was organized by the Czech Technical University in Prague, Faculty of Civil Engineering. It was held in Prague from Wednesday, November 6 to Friday, November 8, 2019 in Czech Institute of Informatics, Robotics, and Cybernetics, located at Prague 6 - Dejvice campus. The conference alternates venue in Slovakia and the Czech Republic. Previous years were in 2004 - Košice, 2005 - Košice, 2006 - Plzeň-Nečtiny, 2007 - Brno, 2008 - Košice, 2009 - Telč, 2010 - Smolenice, 2011 - Olomouc, 2012 - Levoča, 2013 - Kutná Hora, 2014 - Stará Lesná, 2015 - Liberec, 2017 - Košice. The LMP 2019 conference brought together 75 participants from 8 countries (Czech Republic, France, Russia, Slovakia, Germany, Italy, Switzerland, Finland). The conference program covered 36 oral pre- sentations in 8 sections and 21 posters. The conference was supported by 11 generous sponsors whose support is very much appreciated. The conference program consisted of research results and developments in the field of characterization of mechanical properties of various materials at nano- and micro-scales. Wide ranges of materials starting from metals, films and coatings, glass and plastics to biological tissues or structural concrete were covered. The proceedings are composed of selected peer reviewed papers divided into 8 thematic chapters. They include papers from in-situ testing, ceramics and sintered materials, biological materials, coatings and films, cement and building materials, glasses, polymers, fibers, novel alloys and data analysis. The organizing committee hopes that the proceedings will provide a valuable overview and state-of-the-art in the field of local mechanical properties in the countries of Central Europe. The organizing committee would like to thank to all participants and sponsors for their attendance and support. We are looking forward meeting you at LMP 2021 which will be held in Košice, Slovakia. Chairman: Assoc. Prof. Jiří Němeček (Czech Technical University in Prague) Organizing committee: Assoc. Prof. Jiří Němeček (Czech Technical University in Prague) Prof. Petr Haušild (Czech Technical University in Prague) Dr. Radim Čtvrtlík (Palacky university and Institute of Physics Academy of Sciences of the Czech Republic) Jiří Němeček (Czech Technical University in Prague) Pavel Trávníček (Czech Technical University in Prague) Honorary chair: Prof. Ladislav Pešek (SK) Scientific board: Assoc. Prof. Olga Bláhová (CZ) Dr. Jiří Buršík (CZ) Dr. Vilma Buršíková (CZ) Dr. Tomáš Chráska (CZ) Dr. Radim Čtvrtlík (CZ) Prof. Gerhard Dehm (AT) Prof. Petr Haušild (CZ) Prof. Vincent Keryvin (FR) Dr. František Lofaj (SK) Dr. Gaurav Mohanty (FIN) Dr. Aleš Materna (CZ) Dr. David Mercier (FR) Prof. Jaroslav Menčík (CZ) Prof. Michael Swain (AUS) Dr. Pavol Zubko (SK) Prof. Ján Dusza (SK) Dr. Michael Griepentrog (DE) Dr. Maroš Halama (SK) Assoc. Prof. Jiří Němeček (CZ) Prof. Ladislav Pešek (SK) Dr. Ulrich Prahl (DE) Dr. Jiří Matějíček (CZ) Dr. Šárka Houdková Šimůnková (CZ) Guarantor of the peer review process: Jiří Němeček Guarantor of language editing: Jiří Němeček Best poster winners Sylvain Giljean with the poster "Relation between hardness of multilayered (Ti, Al)N based coatings and periods of their stacking". Best poster award was awarded in recognition to scientific quality of the poster. Radim Kudělka, with the poster "Laser-induced surface acoustic waves for thin film characterization". Best poster award was awarded in recognition to application potential of the poster.  Sponsors and Exhibitors Anton Paar Zeiss MTM Měřící Technika Morava Edlin Anamet Metalco Testing Optixs Zwick-Roell Struers Specion Labtech